2013
DOI: 10.1111/vop.12129
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid (vorinostat): its role on equine corneal fibrosis and matrix metalloproteinase activity

Abstract: Suberoylanilide hydroxamic acid (SAHA) can effectively inhibit TGFβ-induced differentiation of equine corneal fibroblasts to myofibroblasts and modulates MMP production in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
(140 reference statements)
1
21
0
Order By: Relevance
“…al. found that SAHA reduced corneal haze in rabbits in vivo following PRK (Bosiack et al 2012, Tandon et al 2012, Donnelly et al 2014). While the efficacy of SAHA as an anti-fibrotic has been repeatedly demonstrated, the precise molecular mechanisms by which it inhibits fibrosis in the cornea have not been extensively investigated so far.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…al. found that SAHA reduced corneal haze in rabbits in vivo following PRK (Bosiack et al 2012, Tandon et al 2012, Donnelly et al 2014). While the efficacy of SAHA as an anti-fibrotic has been repeatedly demonstrated, the precise molecular mechanisms by which it inhibits fibrosis in the cornea have not been extensively investigated so far.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, trichostatin A, an inhibitor of class I and II HDACs, was shown to effectively decrease corneal fibrosis in rabbits in vivo following photorefractive keratectomy surgery (Sharma et al 2009). Another HDACi, suberanilohydroxamic acid (SAHA) which is FDA approved, tested in our laboratory demonstrated significant inhibition of TGF-β1-mediated fibrosis in canine and equine cornea in vitro and rabbit cornea in vivo (Bosiack et al 2012, Tandon et al 2012, Donnelly et al 2014). A recent study from our laboratory found that anti-fibrotic effects of SAHA are partially mediated by the transcriptional repressors 5′TG3′-interacting factors (TGIF) 1 and TGIF2 in human cornea in vitro (Sharma et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…β‐actin was used as the housekeeping gene with the forward primer being CGGCTACAGCTTCACCACCA and the reverse primer being CGGGCAGCTCGTAGCTCTTC. These primers had previously been validated on equine corneal cells . The efficacy of each primer was determined by using each PCR primer expression ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Equine corneal research to date has typically been performed using either in vitro model systems or in vivo studies utilizing a low number of animals . In vitro models utilize monocultures of representative corneal cell populations and cannot fully evaluate potential pathologic and toxic changes that may occur in the multilayered cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Once resolved, the cornea is often left with a scar that leads to a reduction in the visual field. Corneal scar formation is a recognized problem afflicting not only horses, but in many of our domestic animal species, as well as people . This loss of corneal transparency can result in a horse being unable to perform its duties such as racing, jumping, or trail riding and can prove to be dangerous to both itself and his/her handler …”
Section: Introductionmentioning
confidence: 99%